Kinematics and kinetics of the bench press and bench pull in a strength-trained sporting population - Pearson, S.; Cronin, J.; Hume, P.; Slyfield, D. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
A comparison of kinematics and kinetics from the upper body musculature in shoulder flexion (bench press) and extension (bench pull) movements were performed across loads of 10-100%1RM. Twelve elite male sailors with extensive strength-trainingexperience participated in the study. 1RM strength and force were greater in the bench press, while velocity and power output were greater for the bench pull across the range of loads. Pmax for both mean and peak power occurred at a significantly (p<0.000) higher relative load in the bench pull (78.6±5.7% and 70.4±5.4% of 1RM) than the bench press (53.3±1.7% and 49.7±4.4% of 1RM). Findings can most likely be attributed to differences in muscle architecture for shoulder extension/pull and flexion/push movements, which may have training implications for these muscles.